2020
DOI: 10.1101/2020.01.17.910679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-essential function of KRAB zinc finger gene clusters in retrotransposon suppression

Abstract: One Sentence Summary:Megabase-scale deletions of KRAB-ZFP gene clusters in mice leads to retrotransposon activation. AbstractThe Krüppel-associated box zinc finger protein (KRAB-ZFP) family amplified and diversified in mammals by segmental duplications, but the function of the majority of this gene family remains largely unexplored due to the inaccessibility of the gene clusters to conventional gene targeting. We determined the genomic binding sites of 61 murine KRAB-ZFPs and genetically deleted in mouse embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…KRAB-ZPFs are known to regulate VM-IAPs (Bertozzi et al, 2020), and mechanistically, the Mtrr gt locus contains a cluster of 129P2Ola/Hsd-derived KRAB zinc finger proteins (ZFPs) in an otherwise C57Bl/6J background because of the mutagenesis process (Bertozzi et al, 2021). However, the KRAB-ZFP clusters within the Mtrr locus do not appear to regulate RLTR4 expression (Wolf et al, 2020). Others have shown that paternal Mthfr deficiency in mice causes hypomethylation of L1Md subfamily of LINE-1 retrotransposons (Karahan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…KRAB-ZPFs are known to regulate VM-IAPs (Bertozzi et al, 2020), and mechanistically, the Mtrr gt locus contains a cluster of 129P2Ola/Hsd-derived KRAB zinc finger proteins (ZFPs) in an otherwise C57Bl/6J background because of the mutagenesis process (Bertozzi et al, 2021). However, the KRAB-ZFP clusters within the Mtrr locus do not appear to regulate RLTR4 expression (Wolf et al, 2020). Others have shown that paternal Mthfr deficiency in mice causes hypomethylation of L1Md subfamily of LINE-1 retrotransposons (Karahan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular evolutionary arms races are known to play a role in genome size evolution (Ågren and Wright 2015;Kapusta et al 2017;Cosby et al 2019). An arms race in which zinc-finger proteins evolve to bind to and suppress transcription of endogenous retroviruses (ERVs) has been well documented in mammalian genomes (Bruno et al 2019;Wolf et al 2020). Oreochromines have an average amount of zinc-finger proteins compared to other teleosts, but…”
Section: Discussionmentioning
confidence: 99%
“…The family of Krüppel-associated box (KRAB) domain containing zinc finger (ZF) transcriptional regulators has expanded greatly during vertebrate evolution ( 1–3 ), largely in response to a need to repress transposable elements ( 4 , 5 ). Transposable elements make up a large fraction of the genome and are mostly considered genetic threats in need of the strictest silencing during embryogenesis and differentiation.…”
Section: Introductionmentioning
confidence: 99%